Docking of competitive inhibitors to the P2X7 receptor family reveals key differences responsible for changes in response between rat and human. Issue 16 (15th August 2015) - Caseley, Emily A.; Muench, Stephen P.; Baldwin, Stephen A.; Simmons, Katie; Fishwick, Colin W.; Jiang, Lin-Hua
Graphical abstract